Use of Modern Technologies in English Language Teaching Methods - Kulimova Malika Saliyevna (Zien Journals, 2023)
It is no secret that today a number of reforms are being carried out by our President to study foreign languages, especially English. For this reason, in this article, the author discusses in detail the importance of learning foreign languages and methodology of learning English, as well as the ability to use modern technologies in the process of language teaching
Keywords: Foreign language; game; innovative technology; technological tools